The peculiarities of spread and onset of chronic subclinical endometritis in dairy cows - Yaholnyk, M. (Scientific Progress & Innovations, 2025)
Chronic subclinical endometritis is an extremely spread cow disease, which is a rather dangerous and spread pathology in the whole world. Though the disease in cows develops without clearly expressed clinical signs, the animals’ owners and farms, on the whole, notice a considerable effect of the disease both on the animals’ state of health and economic indicators, connected with the keeping of the diseased animals. As a consequence of the disease, dairy productivity and reproductive ability of cows decreases, the farms suffer losses on diagnostic and therapeutic measures, besides, insemination of such cows in the majority of cases is ineffective. The purpose of our paper was to determine the spread and peculiarities of the clinical onset of chronic subclinical endometritis among infertile dairy cows. The work was conducted on dairy industrial farms of different property forms on the territory of Poltava and Kharkiv regions. The study was made on the cows of Red Holstein and Ukrainian local dairy breeds aged from 4 to 8 years. The diagnostics of chronic subclinical endometritis (CSCE) was conducted by gynecological examina-tion of infertile cows on the 60–120th day of lactation and ultra-sonic diagnostics of their reproductive system. It has been found that chronic subclinical endometritis among infertile cows on the farms of Poltava and Kharkiv regions is a frequently diagnosed pathology. The frequency of the disease detection among infertile cows reaches 13.4 %. The pathology was most often diagnosed on those dairy farms, where stable keeping is practiced – 14.9 %. Under the conditions of farms with loose keeping, the percentage of diseased cows is considerably lower – 6.5 %. As a result of conducted gynecological examination and special instrumental methods of research, it was found that the external genitals, vagina, and uterine neck in the diseased cows were without changes, and uterine neck canal was closed. During the stage of the sexual cycle excitation, abundant discharge of estrous mucus from the genitals with slightly noticeable fibers of somewhat turbid mucus was observed in part of animals. Insignificant enlargement of the horn of uterus and tonus decrease of its muscular layer was revealed by rectal examination of the genitals. In 95 % of cows, ovulatory activity with the presence of ovarian follicles and yellow bodies of different maturity degree was found. However, in 5% of animals, chronic synechial salpingitis was registered. The increase in endometrium echogenicity with the dilatation of uterus clearance, the presence of insignificant amount of uniform content in it, the enlargement of the uterine body diameter and changing of its echo-structure up to heterogeneous were found by ultra-sonic uterus examination for CSCE.